Friction reactions induced by selective hydrogenation of textured surface under lubricant conditions - Naizhou Du; Xubing Wei; Xiaowei Li; Zan Chen; Shiqi Lu; Jiaqing Ding; Cunao Feng; Kai Chen; Jianghao Qiao; Dekun Zhang; Kwang-Ryeol Lee; Tiancai Zhang (Friction, 2023)
Abstract The passivation of hydrogen atoms and the conformation of textured surfaces under oil-lubricated conditions are effective strategies to obtain amorphous carbon (a-C) films with extremely low friction. It is critical to understanding the influence mechanism of selective surface hydrogenation on the tribological behaviors of textured a-C film under oil-lubricated conditions. In particular, the interactions of hydrogen atoms and lubricants are confusing, which is enslaved to the in situ characterization technique. The reactive molecular dynamics (RMD) simulations were conducted to analyze the friction response of textured a-C films with selective hydrogenation surfaces under oil-lubricated conditions. The results indicate that the existence of hydrogen atoms on specific bump sites significantly decreases the friction coefficient (μ) of textured a-C film, which is highly dependent on the surface hydrogen content. The repulsion between hydrogen atoms and lubricant molecules prompts the formation of a dense lubricant film on the surface of the mating material. Interestingly, with the enhancement of the surface hydrogen content, the passivation of the friction interface and the repulsion between hydrogen atoms and lubricants play dominant roles in reducing the friction coefficient instead of hydrodynamic lubrication.